MODELS OF THE CONCEPT OF DISABILITY (Scientific journal of the Fergana State University, 2023)
This article conceptually reveals the analysis of the concept of disability. The article also discusses models of disability and reveals their specific aspects. In addition, the importance of legal documents in the Republic of Uzbekistan on the social protection of disabled people is emphasized.